Photodegradation of bisphenol A and related compounds under natural-like conditions in the presence of riboflavin: Kinetics, mechanism and photoproducts - Barbieri, Yanina (2008)
The aerobic riboflavin (Rf)-sensitized photodegradation of the endocrine disruptor 4,40 -isopropylidenebisphenol (bisphenol A, BPA), and of the related compounds 4,40 -isopropylidenebis(2,6-dibromophenol) and 4,40 -isopropylidenebis(2,6-dimethylphenol) has been studied in water and water–methanol mixtures through visible-light continuous photolysis, polarographic detection of oxygen uptake, stationary and time-resolved fluorescence spectroscopy, time-resolved near-IR phosphorescence detection and laser flash photolysis techniques. Bisphenols (BPs) quench excited singlet and triplet states of Rf, with rate constants close to the diffusion limit. BPs and dissolved molecular oxygen, employed in similar concentrations, competitively quench triplet excited Rf. As a consequence, superoxide radical anion and singlet molecular oxygen (O2( 1 Dg)) are produced by electron- and energy-transfer processes, respectively, as demonstrated by auxiliary experiments employing selective quenchers of both oxidative species and the exclusive O2( 1 Dg) generator Rose Bengal. As a global result, the photodegradation of Rf is retarded, whereas BPs are degraded, mainly by an O2( 1 Dg)-mediated mechanism, which constitutes a relatively efficient process in the case of BPA. Oxidation, dimerization and fragmentation products have been identified in the photooxidation of BPA. Results indicate that BPs in natural waters can undergo spontaneous photodegradation under environmental conditions in the presence of adequate photosensitizers.